A new analytical model for viscous wall dampers and its experimental validation. (15th May 2018) - Zhou, Ying; Chen, Peng; Zhang, Dan; Gong, Shunming; Lu, Wensheng
Highlights: Quasi-static tests on viscous wall dampers (VWDs) with new material are conducted. A generalised Maxwell model for VWDs with time-varying parameters is proposed. Shake table tests on a 3-storey steel frame with VWDs are conducted. The proposed VWD model is implemented and validated numerically. Abstract: This paper presents a new analytical model for viscous wall dampers (VWDs) and their effectiveness in reducing seismic structural distress. A series of performance tests on VWDs is conducted to measure the response of the dampers under various loading conditions. Based on the non-linear responses elicited in these mechanical tests, a generalised Maxwell model for VWDs with time-varying stiffness and damping is proposed to assess their amplitude dependencies. Shaking table tests are conducted on a 3-storey steel space frame at a 1:4 scale with and without VWDs, using three types of earthquake excitations, to study the effectiveness of these devices. The additional stiffness of VWDs can significantly increase the natural frequencies of the steel frame, and the effect of vibration control on the displacements of the structural model is remarkable. The added damping contributed by VWDs can significantly reduce the acceleration responses and the inter-storey shear forces of the steel frame. The proposed VWD model is implemented using the OpenSees software, and is subsequently used for the dynamic simulation of the shaking table tests. The effectiveness and good adaptability of the proposed model are verified based on the agreement between the numerical simulation and shaking table test results.